PEMANFAATAN WADAH BERBAGI PENGETAHUAN DAN KUALITAS MEREK TERHADAP PERILAKU LOYALITAS KONSUMEN - Sam Oudom Serick; Bambang Purwoko; Derriawan Derriawan; Lingga Yuliana (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2021)
In this study, a brand of herbal medicine called Red Kank (cancer suppression) was initially described strongly as a cancer reducer but has now evolved into cancer-fighting products, such as health and beauty products. This strategic step has not been able to answer whether it leads to its success. Still, it opens the possibility to assess the quality of brand relationships, use of knowledge sharing platforms and their impact on consumer loyalty behavior Red Kank. Primary data were collected using a purposive sampling technique from Jakarta, Bekasi, Surabaya, and Balikpapan customers. The data analysis use Structural Equation Modeling (SEM) by Lisrel 8.7. Statistical results show that the quality of the brand relationship is closely related to the image of the quality of the product itself. Therefore, the company's strategy to diversify begins with increasing understanding of product brands to become company brands.